Factors influencing IT-business strategic alignment and sustainable competitive advantage: A structural equation modelling approach - Almajali, Dmaithan Abdelkarim; Md Dahalin, Zulkhairi (IBIMA Publishing, 2011)
Preceding research attributed the lack of direct causal impact of Information Technology (IT) on firm’s sustainable competitive advantage. Numerous missing links include antecedents of the ITbusiness strategic alignment (also known as strategic alignment) and the sustainable competitive advantage.Furthermore, reviewers of recent literature have called for more research into the factors that affect strategic alignment, and the linkage between alignment and sustainable competitive advantage. In this paper, we develop and empirically test specific forms of management structures and processes which are required to drive strategic alignment. Further, we propose a causal-chain model to examine the impacts of six antecedents on strategic alignment. The data are collected from over 172 Jordanian public shareholding firms. Using structural equation modeling for data analysis, this study finds general support for the hypotheses that leadership, values and belief, IT managerial resources, service quality, and IT implementation successes significantly impact IT-business strategic alignment. However, no relationship is found between structure and process and strategic alignment.